Upaya Guru BK dalam Membimbing Motivasi Belajar Siswa yang Memiliki Kehadiran Rendah di SMP - Lamanele, Dionisius Bayo; Rohi, Enasely Mega Wenyi (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
Teachers and students are fundamental elements in the teaching and learning process. Teaching and learning activities cannot take place if one of these elements is missing. Teachers in junior high schools experience significant problems related to low student attendance. Many internal and external variables contribute to this problem. Therefore, teachers must contribute to solving this problem. The purpose of this study is to determine how the Guidance and Counseling Teachers' Efforts in Guiding the Learning Motivation of Students with Low Attendance in junior high schools. The methodology used is descriptive qualitative research. Teachers in junior high schools were interviewed for this study to learn more about their responsibilities regarding student absence. Questions focused on the issue being studied were used during the interviews. So, based on the research that the author has done, the efforts and strategies that guidance and counseling teachers do in junior high schools that are effective and efficient are by conducting home visits or direct visits to students' homes and establishing good interactive relationships between teachers and parents.